The Impact of Obesity and Lifestyle on the Immune System and Susceptibility to Infections Such as COVID-19 - de Frel, Daan L.; Atsma, Douwe E.; Pijl, Hanno; Seidell, Jacob C.; Leenen, Pieter J. M.; Dik, Willem A.; van Rossum, Elisabeth F. C. (Frontiers in Nutrition, 2020)
Background: COVID-19 is a global challenge to healthcare. Obesity is common in patients with COVID-19 and seems to aggravate disease prognosis. In this review we explore the link between obesity, chronic disease, lifestyle factors and the immune system, and propose societal interventions to enhance global immunity. Search Strategy and Selection Criteria: We performed three literature searches using the keywords (1) coronavirus AND comorbidities, (2) comorbidities AND immune system, and (3) lifestyle factors AND immune system. Results were screened for relevance by the main author and a total of 215 articles were thoroughly analyzed. Results: The relationship between obesity and unfavorable COVID-19 prognosis is discussed in light of the impact of chronic disease and lifestyle on the immune system. Several modifiable lifestyle factors render us susceptible to viral infections. In this context, we make a case for fostering a healthy lifestyle on a global scale. Conclusions: Obesity, additional chronic disease and an unhealthy lifestyle interactively impair immune function and increase the risk of severe infectious disease. In adverse metabolic and endocrine conditions, the immune system is geared toward inflammation. Collective effort is needed to ameliorate modifiable risk factors for obesity and chronic disease on a global scale and increase resistance to viruses like SARS-CoV-2.